Direito à saúde : por uma prestação ética do Estado - Alves, Danielle Garcia (2016)
This master thesis is intended to analyze the right to health from the standpoint of ethics provision by the State, having as main objective the promotion of the welfare of the human being and the consequent dignified existence. Considering the principle of human dignity as a guide, outlines to the historical evolution of human rights and the rise of the right to health the category of fundamental social rights, particularly in the provision of health services in Brazil. We seek to understand the health delivery model adopted in the country, which necessarily involves the analysis of the structure of entities providers of public administration. In this sense, we analyze the performance of Public Administration Network, always in search of good governance that enables the effective and efficient delivery of the right to health. On the other hand, and in the face of increasingly present role of the judiciary in health-related issues, the objective is to see if this legalization solve the problem or turns out to further promote inequality, as access to justice in Brazil has not yet reached desirable levels. The study aims to discuss how ethics, bioethics and justice, using the ethical model of the responsibility of Hans Jonas, can contribute to increased quality of the provision of national public health, in order to guarantee the right to decent life This generation and also future.